Full-factor matrix model of accuracy of dimensions performed on multi-purpose CNC machines - Yusubov, Nizami; Abbasova, Heyran (Novosibirsk State Technical University, 2021)
One of the main reasons that modern multi-purpose CNC machines do not use the capabilities of multi-tool processing is the lack of recommendations for design in this direction and, accordingly, for adjustment schemes. The study of the possibilities of multi-tool processing on multi-purpose machines is the subject of the work. The purpose of research: The problem of developing full-factor matrix models of dimensional accuracy and its sensitivity to the machining process is considered to increase the machining effi ciency while ensuring machining accuracy using the technological capabilities of multi-tool machining on modern multi-purpose CNC machines. For this purpose, full-factor matrix models of the size scattering fi elds performed on multi-tool double-carriage adjustments have been developed, taking into account the cases of processing parts with dimensions that differ sharply in different directions, which are often encountered in practice, and in this case, the signifi cant infl uence of the turns of the workpiece on the processing error, especially in directions with sharply different overall dimensions. Results of research: The developed accuracy models make it possible to calculate not only plane-parallel displacements of the technological system for double-carriage adjustments, but also angular displacements around base points, take into account the combined effect of many factors – a complex characteristic of the subsystems of the technological system (plane-parallel matrix of compliance and angular matrix of compliance), the geometry of the cutting tool , the amount of bluntness of the tool, cutting conditions, etc. As a result, based on the developed accuracy models, it is possible to obtain several ways to control multi-tool machining, including improving the structure of multi-tool adjustments, calculating the limiting values of cutting conditions. Based on the developed full-factor matrix models, it became possible to develop recommendations for the design of adjustments and the creation of an automated design system for multi-tool machining for a group of modern multi-purpose CNC lathes. Scope of the results: The results obtained can be used to create mathematical support for the design of operations in CAD-systems provided for multi-tool multi-carriage machining performed on multi-purpose machines. Conclusions: The developed models and methodology for simulating the machining accuracy make it possible to increase the accuracy and effi ciency of simultaneous machining, to predict the machining accuracy within the specifi ed conditions.
Keywords: Multi-purpose CNC machines